Perenialism and Islamic Religious Education: The Philosophical Perspectives of Key Thinkers and Their Relevance to Contemporary Islamic Religious Education - Marzuki; Zulkifli Musthan; Muh. Saleh (IAIN KENDARI, 2026)
Perennialism encompasses fundamental concepts that significantly influence Islamic religious education. This study examines perennialism as a philosophical framework and its contributions to Islamic education. This study examines the concepts of significant perennialist thinkers such as Seyyed Hossein Nasr, Frithjof Schuon, and Ananda Coomaraswamy through a qualitative literature review. The findings indicate that perennialism emphasises the universality of spiritual truth, the integration of divine knowledge, and the significance of tradition in Islamic education. This approach prioritises the development of inner spirituality and moral values over contemporary secular education. The study posits that Islamic education must revise its curriculum to align with perennialist concepts.